The Multimodal Perception of Contrastive Focus in French: A Developmental Study - Rapin, Lucile; Ménard, Lucie (Frontiers in Communication, 2019)
The current study aimed to better understand the development of prosody perception, by investigating the audiovisual, audio, and visual perception of contrastive focus in French-speaking adults and children. Specifically, 20 adults and 20 school-aged children were presented with short sentences in audiovisual, audio, and visual modalities and were asked to determine if the sentences were produced under neutral or contrastive focused speech. Target words incorporated into the sentences varied across four vowels: /i y u a/. Overall, the adults performed significantly better than the children. Moreover, the children relied more on duration cues to identify contrastive focus, while the adults relied more on formant and lip height values. These findings suggest that children acquire visual cues of speech perception as they mature.